EFL STUDENTS’ PERCEPTION REGARDING THE UTILIZATION OF TED (TECHNOLOGY, ENTERTAINMENT, AND DESIGN) TALKS TO ENHANCE THEIR SPEAKING SKILLS - Berliana Sukma Tri Sukarno; Mukhlash Abrar; Saharudin Saharudin; Marzul Hidayat (IKIP Siliwangi, 2024)
This qualitative study investigates the perception of English as a Foreign Language (EFL) students regarding the utility of TED Talks in improving their speaking proficiency. Through interviews and documentation analysis, the study addresses the central query: